Efektivitas Mekanisme Tripartit dalam Penyelesaian Sengketa Ketenagakerjaan di Indonesia - Nikmah Dalimunthe; Raiva Safwah (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study examines the effectiveness of the tripartite mechanism in resolving industrial relations disputes in Indonesia amid unequal bargaining positions between workers and employers. Normatively, the tripartite mechanism is designed as a dialogical, efficient, and relatively low-cost non-litigation dispute resolution instrument. This research employs a qualitative descriptive approach through library research by analyzing legislation, international conventions, scholarly journals, and relevant official documents. The findings indicate that although the legal framework of the tripartite mechanism is comprehensive, its implementation remains constrained by limited professionalism of mediators and conciliators, procedural dominance, and unequal industrial relations, which contribute to the escalation of disputes to arbitration. The study concludes that strengthening the competence of tripartite actors and integrating principles of substantive justice, including justice, wisdom, and responsibility from an Islamic law perspective, are essential to enhance the effectiveness of industrial dispute resolution in Indonesia.